Analysis of Corporate Social Responsbility Program of Bank Sumsel Babel Lahat Branch in Improving the Corporate Image - Agustini, Rahma Sarita; Setyaningsih, Rila; Siva, Nur (Asian Journal of Management Analytics, 2025)
Corporate communication activities are key in maintaining a company's business reputation . Corporate Social Responsibility is one of the corporate communication activities that can be carried out to maintain a company's good reputation . This research aiming to analyze the impact of the Corporate Social Responsibility (CSR) program run by Bank SumselBabel Lahat Branch in improving the company's image .This research method uses a qualitative descriptive method with a Stimulus- Response (SR) concept approach . Data was collected through observation , in-depth interviews,and document analysis . The results of this research showed that the Bank SumselBabel Lahat Branch CSR program had a significant impact value on increasing the company's reputation . CSR activities that focused on economic empowerment of local community , education and regional development were well received by the local community . apart from that , the CSR program carried out by Bank SumselBabel Lahat Branch has succeeded in increasing closer relations between the community and the bank, which in the end can attract potential new customers and increase customer loyalty .